The effect of applying resource consumption accounting technology on rationalizing pricing decisions in economic units (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The aim of the research is to demonstrate the extent of the impact of resource consumption accounting technicality as an administrative technique that is compatible with the rapid developments and changes in the external environment, with the information it provides and scientific foundations in the allocation of indirect costs, and the identification and measurement of idle energy and its costs in a way that contributes to the rationalization of pricing decisions in economic units. In light of the intense competition and the multiplicity of alternatives, and to achieve this goal, a random sample was chosen.